2022
DOI: 10.3934/publichealth.2022050
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of quality of work life in private hospitals in Enugu, Nigeria: A qualitative study

Abstract: <abstract> <p>Despite being essential for retaining nurses, not much is known about nurses' quality of work life (QWL) in private hospitals in sub-Saharan Africa, including Nigeria. We explored nurses' perceptions of QWL, factors influencing it, how it affects motivation, and strategies for its improvement. The study was conducted in seven private hospitals in Enugu, Nigeria. The design was qualitative, using focus group discussion (n = 7) with registered nurses (n = 66) purposively selected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…For example, in Nigeria, seven focus groups consisting of 66 nurses reported that long work hours and burnout were factors leading to job cessation [ 23 ]. Similarly, a survey of 2428 nurses from 32 hospitals in Malaysia found that one in four nurses reported burnout, and shift working, double-shifts, and night shifts were associated with burnout [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Nigeria, seven focus groups consisting of 66 nurses reported that long work hours and burnout were factors leading to job cessation [ 23 ]. Similarly, a survey of 2428 nurses from 32 hospitals in Malaysia found that one in four nurses reported burnout, and shift working, double-shifts, and night shifts were associated with burnout [ 24 ].…”
Section: Discussionmentioning
confidence: 99%